An Empirical Study on the Integration of Modern Educational Practices in Salaf Islamic Boarding Schools: Challenges, Resistance, and Strategies for Implementation - Nikmatus Sholihah; Mas Ayu Ainun Nisa'; Muhammad Adib Nuruzzaman; Achmad Zaini (JURNAL AT-TURAS, 2025)
This study examines the education policy at the Fathul Hidayah Pangean Lamongan Islamic Boarding School in dealing with resistance to the integration of traditional and modern education. Using a qualitative approach and thematic analysis of in-depth interview data and participant observation, this study attempts to understand how the Islamic boarding school manages the dynamics of change. The results of the study indicate that although there is resistance from some conservative groups towards elements of modern education, the integrative policy implemented has succeeded in creating a balance between religious and general education. The Islamic boarding school is able to develop a horizontal integration curriculum (religious and general knowledge) with a contextual approach, preparing students to face global challenges without losing their Islamic identity. The main contributions of this study include: (1) the proposal of a curriculum integration model based ontwin track paradigmwhich combinesdeep religious literacy and functional competencies; (2) development of a participatory framework to manage resistance through dialogue between stakeholders; and (3) policy recommendations for Islamic boarding schools to be adaptive and collaborative in the process of modernizing education. Nationally and globally, rejection of educational integration is a strategic issue because it is closely related to cultural identity and readiness to face globalization. The tension between preserving religious values and the demands of modernization is a real challenge for Islamic educational institutions. This research opens up space for further studies, such as testing the effectiveness of the curriculum integration model or developing indicators of success for salaf-modern integration in various social contexts.